(untitled) (Iraqi Journal of Medical Sciences, 2022)
Background: Coronavirus disease 2019 (COVID-19) is an epidemic disease produced via the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) beta coronavirus, which affects the lower respiratory tract. Secondary bacterial infection (SBI) is a serious and public problem in patients hospitalized with COVID-19 and caused 50% of deaths. Type A and O blood groups are more susceptible to infection with SBIs. Objective: To examine the relationship between SBI and ABO blood group with COVID-19 hospitalized patients in Baghdad and Diyala province. Methods: Three hundred and forty-two patients with COVID-19 were collected from several sources (nasal swab, pharyngeal swab, sputum, blood, and urine) of patients of different ages for the period between September to November 2021. Real-time reverse-transcription polymerase chain reaction technique was used to diagnose COVID-19 in the patients as well as selective and differential media, biochemical tests BACT/ALERT system, and VITEK 2 compact system were used to diagnose the isolates of SBIs. The disk diffusion technique was used to assess the susceptibility test of all isolates. ABO group analysis was done for totally patients with COVID-19 under the study. Results: Antimicrobial sensitivity test showed all SBIs were highly strong resistant to antibiotics. Fifty-seven isolates of bacteria were diagnosed including Staphylococcus aureus, Pseudomonas aeruginosa, Acinetobacter baumannii, Klebsiella pneumoniae, and Escherichia coli. Group A and O showed a higher rate of acquired SBIs. Duration of infection with COVID-19 showed 61% for 10 days and 30% for one month while 9% in the patients infected with SBI for more than one month. The result appeared that SBIs infection at were very high rate in COVID-19 patients who had untreated antibiotics compared with the patient treated with antibiotics through the duration of infection. Conclusion: The study revealed that many COVID-19 patients were more susceptible to infection with SBIs, especially in the early days of infection as well as there was a correlation between ABO blood groups and SBIs of COVID-19 patients. Keywords: COVID-19; SBIs, AST, ABO blood group Citation: Albadri AF, Alzubaidy ZM. Investigation of the prevalence of secondary bacterial infection associated with COVID-19 in Baghdad and Diyala province. Iraqi JMS. 2022; 20(2): 252-261. doi: 10.22578/IJMS.20.2.13